Maintenance strategy of multicomponent system based on structure updating and group importance measure. Issue 9 (25th March 2022) - Chen, Yijie; Feng, Hailin
Abstract: For a multicomponent system, a maintenance strategy based on system structure updating and group importance measure is proposed. First, a system structure is determined by redefining its component grades, furthermore, the system structure updating is realized by introducing its survival signature. And based on the current system structure, a corrective maintenance that combines sequentially minimal repair with corrective replacement is formulated. Second, a two-level preventive maintenance (PM) is formulated based on a new group importance measure which is designed by considering two indicators, one is the system reliability calculated through its survival signature, the other is PM costs. The two indicators are calculated after its several components are updated preventively. Then, a cost-rate model is developed to find the optimal maintenance strategy. Finally, 6-component system and 10-component system are given to demonstrate the performance of the proposed strategy, and the result shows the strategy leads to significant profits when compared with existing strategies.